Organotin(IV) carboxylates - derivatives of bexarotene: synthesis, characterization, anti/prooxidant activity, and high cytotoxicity - Burmistrova, Daria; Pomortseva, N. P.; Berberova, N. T.; Almyasheva, N. R.; Kiskin, M. A.; Poddel'sky, Andrey; Vashurin, A. S.; Smolyaninov, I. V. (Journal of biological inorganic chemistry, 2025)
New organotin(IV) mono- and bis-carboxylate complexes derivatives of Bexarotene (bex), viz. R3Sn(bex) (where R = Ph (1); Cy (2); nBu (3)), and R2Sn(bex)2 (where R = Et (4), tBu (5), Ph (6)) were synthesized. Compounds were fully characterized using spectroscopic techniques. The molecular structure for the Ph3Sn(bex) (1) in crystalline form was established by single-crystal X-ray diffraction. Electrochemical properties of tin complexes and bexarotene were investigated by cyclic voltammetry. The target compounds are characterized by the high oxidation potentials in the mixture of aprotic solvents. The anti/prooxidant activity of the complexes and bexarotene in the lipid peroxidation process and in the reaction of the DNA oxidative damage was studied in vitro. Excellent cell growth inhibition against A549, HCT 116 and MCF-7 cancer cells was observed for triorganotin (IV) carboxylates with IC50 values mostly under the submicromolar concentration range and there are more effective than bexarotene or cisplatin.
Online veröffentlicht: 04. Juni 2025
Gesehen am 15.09.2025